2020
DOI: 10.1088/2053-1591/ab6c5e
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticle from pomelo (Citrus Maxima) and their antibacterial activity against acidovorax oryzae RS-2

Abstract: Silver nanoparticles (AgNPs), synthesized with plant materials, are considered to be an emerging field of agriculture for their eco-friendly and outstanding antibacterial attributes. In this study, we synthesized AgNPs using pomelo (Citrus maxima) fruit extract as a biological capping and reducing material. The particle size was determined as 11.3-12.8 nm by using UV-vis spectrophotometer, TEM and x-ray diffraction analysis. UV-vis spectrophotometer analysis also confirmed the formation of AgNPs in colloidal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
(62 reference statements)
0
12
0
1
Order By: Relevance
“…The effect of synthesized AgCl-NPs solution on the swarming motility of cells of strain YY06 was examined in the LB broth supplemented with 0.7% ( w / v ) agar [ 53 ], and on swimming motility of the test bacteria in LB broth containing 0.3% agar [ 27 ]. Briefly, 5, 10, and 20 µg/mL −1 of synthesized AgCl-NP solution was mixed with both all LB media at 45 °C in separate petri plates, and 30 µL of the CFCS or ddH 2 O was used as controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of synthesized AgCl-NPs solution on the swarming motility of cells of strain YY06 was examined in the LB broth supplemented with 0.7% ( w / v ) agar [ 53 ], and on swimming motility of the test bacteria in LB broth containing 0.3% agar [ 27 ]. Briefly, 5, 10, and 20 µg/mL −1 of synthesized AgCl-NP solution was mixed with both all LB media at 45 °C in separate petri plates, and 30 µL of the CFCS or ddH 2 O was used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…To observe the interaction of the AgCl-NPs with pathogenic bacterium cells, we observed morphological changes on the surfaces of bacterial cells by SEM after the AgCl-NPs treated bacterial cells with final concentration of 2.0 µg/mL −1 with shaking (200 rpm) at 30 °C for 4 and 8 h. Briefly, suspensions of the treated bacteria were centrifuged at 6000 rpm for 10 min at 4 °C, washed with PBS at pH 7, post-fixated in 1% ( w / v ) osmium tetroxide, and dehydrated in a graded ethanol series (50%, 70%, 80%, 90%, 95%, and 100%), as described by [ 53 ]. The samples were attached to an aluminum stub and sputter-coated with gold, and then examined and photographed in an SEM (Zeiss Gemini SEM 300, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The study revealed the importance of biosynthesized AgNPs, which can play a significant role in controlling Acidovorax oryzae strain RS-2. AgNPs downregulate the expression of type VI secretion system allied genes, which affects the virulence of bacteria [ 229 ]. Global efforts are underway to reduce the use of dangerous substances, especially chemical pesticides, in crop production.…”
Section: Applications Of Agnpsmentioning
confidence: 99%
“…e flavonoids in pomelo peel extract can reduce silver ions into metallic Ag particles, and pectin can cap the formed AgNPs to protect them from further growth in size. To the best of our knowledge, only few studies used pomelo juice or pomelo peel extract to synthesize AgNPs, and none of these studies utilized sunlight to assist the formation of AgNPs [22][23][24]. erefore, we studied the formation of AgNPs in PPE upon exposure to direct sunlight and characterize the synthesized AgNPs, including their stability against electrolyte-induced agglomeration and antibacterial activity against four bacterial strains.…”
Section: Introductionmentioning
confidence: 99%